(untitled) (Revista de Ciências Agroveterinárias, 2023)
The use of herbicides for weed control is the most used method due to its effectiveness, speed, and lower cost, but few products are registered for canola crops. In this way, the objective of this work was to evaluate the selectivity (experiment 1) and efficiency (experiment 2) of herbicides applied alone or in association in pre‑ and post-emergence of canola for weed control. The experiments were carried out in randomized blocks design, with four replications. In pre-emergence, the herbicides oxyfluorfen, pendimethalin, flumiozaxin, and trifluralin were applied, and in post-emergence, fluazifop-p-butyl, plus weeded and infested controls. Phytotoxicity and physiological characteristics were evaluated in the selectivity experiment, and the control of turnip, ryegrass, and black oat weeds were evaluated in the efficacy experiment. In both experiments, the number of siliques per plant, grains per silique, plant density, thousand-grain weight, and grain yield were determined. Oxyfluorfen applied alone or associated with fluazifop-p-butyl caused the highest phytotoxicity to the Diamond canola hybrid. The lowest phytotoxicities were observed for pendimethalin and fluazifop-p-butyl applied alone or in an association. All tested herbicides caused stress on internal CO2 concentration, transpiration, stomatal conductance, photosynthetic activity, water use efficiency, and carboxylation efficiency. Flumioxazin and fluazifop-p-butyl applied pre- and post-emergence of canola showed the best results for the crop yield components, especially higher productivity, also with the weeded control in the selectivity experiment. None of the herbicide treatments controlled turnip properly (experiment 2), and the presence of this weed negatively affected canola yield components. Fluazifop-p-butyl applied alone or in association with oxyfluorfen, pendimethalin, flumioxazin, and trifluralin showed the best controls of ryegrass and black oat.